transcriptome sequencing and gene expression profiling with/without B-chromosome plants of - Doori Park; Jong-Hwa Kim; Nam-Soo Kim (Genomics & Informatics)
Supernumerary B chromosomes were found in Lilium amabile (2n = 2x = 24), an endemic Korean lily that grows in the wild throughout the Korean Peninsula. The extra B chromosomes do not affect the host-plant morphology; therefore, whole transcriptome analysis was performed in 0B and 1B plants to identify differentially expressed genes. A total of 154,810 transcripts were obtained from over 10 Gbp data by de novo assembly. By mapping the raw reads to the de novo transcripts, we identified 7,852 differentially expressed genes (log2FC > |10|), in which 4,059 and 3,794 were up-and down-regulated, respectively, in 1B plants compared to 0B plants. Functional enrichment analysis revealed that various differentially expressed genes were involved in cellular processes including the cell cycle, chromosome breakage and repair, and microtubule formation; all of which may be related to the occurrence and maintenance of B chromosomes. Our data provide insight into transcriptomic changes and evolution of plant B chromosomes and deliver an informative database for future study of B chromosome transcriptomes in the Korean lily.